2021
DOI: 10.3390/vaccines9050500
|View full text |Cite
|
Sign up to set email alerts
|

Intention to Be Vaccinated for COVID-19 among Italian Nurses during the Pandemic

Abstract: Background: While the COVID-19 pandemic has spread globally, health systems are overwhelmed by both direct and indirect mortality from other treatable conditions. COVID-19 vaccination was crucial to preventing and eliminating the disease, so vaccine development for COVID-19 was fast-tracked worldwide. Despite the fact that vaccination is commonly recognized as the most effective approach, according to the World Health Organization (WHO), vaccine hesitancy is a global health issue. Methods: We conducted a cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 30 publications
3
34
0
Order By: Relevance
“…This strategy has not been studied and could expose people to incomplete protection for a long time. Such considerations are especially important when programming vaccine campaigns for workers exposed to high risk [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…This strategy has not been studied and could expose people to incomplete protection for a long time. Such considerations are especially important when programming vaccine campaigns for workers exposed to high risk [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Women were more likely to report conditions, and physicians were less likely to report them. Most of the available studies reported results based on surveys investigating hesitancy before COVID-19 vaccination uptake [7][8][9][10][11][12][13], while our analysis is based on multiple real-time surveys obtained through the forms compiled on the very day of the vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies indicate 70% as the threshold for heard immunity [14]. Different surveys collected data on the intention to receive the COVID-19 vaccine, with refusal rates between 10% and 23% among HCWs and students [9][10][11]. Of the 1546 participants of a study conducted among Qatari HCWs, 61% reported to receive flu vaccine annually, and more than 60% referred chronic conditions, though only 12% of those in the hesitant group reported any.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the rate of vaccination refusal among HCWs remains relevant for different reasons. As an example, we report the lack of confidence in vaccines (and fear of the potential hazards, including misconceptions about the risk of infection following vaccination), a poor understanding of the need to vaccinate (e.g., underestimation of disease severity), the fear of the potential side effects, political or religious influences, difficulties in accessing the vaccine and misinformation [ 13 ].…”
Section: Introductionmentioning
confidence: 99%